Effect of Various Substrates on Growth and Yield Performance of Oyster Mushroom (Pleurotus ostreatus) in Chitwan, Nepal - Sitaula, Hom Prasad; Dhakal, Roshan; DC, Geetesh; Kalauni, Dharmendra (International Journal of Applied Sciences and Biotechnology, 2018)
An experiment was conducted at Rampur, Chitwan, Nepal to find out the growth and yield performance of oyster mushroom (Pleurotus ostreatus) in Completely Randomized Design (CRD).The treatment includes the four different substrate i.e. paddy straw (100%), maize cob+ paddy straw (1:1), sugarcane bagasses+paddy straw (1:1) and sawdust+ paddy straw (1:1). The parameters taken for the observation during the experiment were colonization period, fruit initiation period, length of stalk, diameter of stalk, diameter of pileus, fresh weight of the first and second flush of mushroom and also the biological efficiency (BE) of various substrates. Among the used substrates, the time for colonization and fruit initiation was found to be shorter in case of the paddy straw i.e.18.25 days and 21.75 days respectively. However, the length of stalk was highest in sugarcane bagasses+paddy straw (1:1) i.e.6.10 cm, but the diameter of stalk and pileus were highest in paddy straw i.e.0.80 cm and 7.90 cm respectively. Similarly, the biological efficiency was found to be highest in case of the paddy straw (96.29688%) followed by maize cob+paddy straw (1:1), sugarcane bagasses+ paddy straw (1:1) and sawdust+ paddy straw (1:1) respectively. Int. J. Appl. Sci. Biotechnol. Vol 6(3): 215-219